Magnoliae flos Downregulated Lipopolysaccharide-Induced Inflammatory Responses via NF-κB/ERK-JNK MAPK/STAT3 Pathways - Tae-Young Gil; Bo-Ram Jin; Yun-Yeop Cha; Hyo-Jin An (Hindawi Limited, 2022)
Background. Magnoliae flos is the dried flower bud of Magnolia biondii and related plants. It has been used as a medicinal herb for the treatment of rhinitis, sinusitis, and sinus headaches. Nevertheless, the effects of Magnoliae flos in microbial infection or sepsis remain unclear. In this study, we investigated the anti-inflammatory effects of Magnoliae flos water extract (MF) in lipopolysaccharide- (LPS-) induced septic mice and LPS-stimulated RAW264.7 macrophages. Results. We found that MF reduced the mortality of LPS-challenged mice. Enzyme immunoassays and reverse transcription polymerase chain reaction analysis revealed that MF administration attenuated mRNA expression and protein production of proinflammatory mediators, including cyclooxygenase 2, inducible nitric oxide synthase, tumor necrosis factor-α, and interleukin-6. In parallel to these results in mice, pretreatment with MF suppressed the LPS-induced production of proinflammatory mediators in RAW264.7 macrophages. In addition, we found that MF exerted its suppressive effects by inhibiting the activation of the mitogen-activated protein kinase, nuclear factor-κB, and signal transducer and activator of transcription pathways at the protein level. Conclusion. MF could be a potential therapeutic agent for regulating excessive inflammatory responses in sepsis.